Qualitative assessment of individuals at a family health center: avoidance/refusal of COVID-19 vaccination: - SiL, Ertan; Mazıcıoğlu, Mümtaz; Nahya, Nilüfer; Bilgici, Ethem (General Practice, 2024)
Background. The avoidance or refusal of vaccines is a significant public health problem during the COVID-19 pandemic. This article focuses on vaccine avoidance and refusal among patients at a Family Health Center (FHC). We will attempt to identify and describe the factors that contribute to avoidance and refusal so that new strategies can be developed. Methods. This study was conducted between December 2021 and August 2022. Eight individuals were interviewed with a semi-structured form. The study cite was Turgut Reis FHC Kayseri/Turkey. Thematic analysis was used to analyze the qualitative data. Results. The study identified three main themes and 16 sub-themes based on verbatim notes. The main themes were the level of knowledge regarding COVID-19 and individual and non-individual factors causing COVID-19 vaccine avoidance/refusal. Some of the sub-themes included the reality of the disease, protective measures, concerns about the content and production process of the vaccine, the interaction between chronic disease and COVID-19, and the positive or negative effects of religion and national identity on vaccination. The study demonstrated that concerns about vaccine safety, efficacy, and production, as well as individual preferences, media influence, and mandatory regulations of health care management were the most influential factors in vaccine avoidance/refusal. Conclusions. The sudden onset of COVID-19 resulted in a delayed response from society and health authorities. This delay may be due to distrust of the disease, reluctance to adopt preventive measures, and uncertainty about treatment options. While advanced technology exists, limited public information about the vaccine’s effectiveness and production processes could be contributing to this reaction.